2020
DOI: 10.1152/ajplung.00161.2020
|View full text |Cite
|
Sign up to set email alerts
|

Urgent reconsideration of lung edema as a preventable outcome in COVID-19: inhibition of TRPV4 represents a promising and feasible approach

Abstract: Kuebler WM, Jordt SE, Liedtke WB. Urgent reconsideration of lung edema as a preventable outcome in COVID-19: inhibition of TRPV4 represents a promising and feasible approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 50 publications
(63 reference statements)
1
43
0
Order By: Relevance
“…Therefore, patients with low serum calcium might have impaired hemostatic mechanisms. And one study suggested that the occurrence of pulmonary edema in COVID-19 patients may be related to the radio-permeable TRPV4 channel, and the pulmonary edema caused by the virus can be alleviated by TRPV4 inhibitors (31). In one case-cohort research, serum Ca was proofed to be inversely In conclusion, low calcium is not only the electrolyte imbalance caused by viral infection, but also one of the key factors causing multi-organ injury, and it may help to judge the severity of disease in the early stage of virus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with low serum calcium might have impaired hemostatic mechanisms. And one study suggested that the occurrence of pulmonary edema in COVID-19 patients may be related to the radio-permeable TRPV4 channel, and the pulmonary edema caused by the virus can be alleviated by TRPV4 inhibitors (31). In one case-cohort research, serum Ca was proofed to be inversely In conclusion, low calcium is not only the electrolyte imbalance caused by viral infection, but also one of the key factors causing multi-organ injury, and it may help to judge the severity of disease in the early stage of virus.…”
Section: Discussionmentioning
confidence: 99%
“…Control of pulmonary edema is crucial in limiting the severity of ARDS ( 58 ). In this light, TRPV4 channels in the alveolo-capillary unit were recently proposed to be a pharmacologically tractable target for treatment of ARDS associated with COVID-19 ( 30 ). In addition to direct control of lung barrier function by TRPV4 inhibitors, there is evidence that TRPV4 channels could induce PANX1 channel activity ( 45 , 49 , 50 ), suggesting that PANX1 inhibitors might improve the efficacy of TRPV4 channel inhibitors.…”
Section: Regulation Of Inflammation By Panx1 In the Context Of Covid-mentioning
confidence: 99%
“…Although TRP channels have no role in healthy lung function, repair processes use them to promote endothelial permeability, inducing inflammation for immune action, which are normal helper processes. Still, again their activation could become pathological [326], involved in asthma, COPD, and pulmonary fibrosis [327] and pulmonary edema [328].…”
Section: The Hypothesismentioning
confidence: 99%